2014
DOI: 10.5539/ijps.v6n4p26
|View full text |Cite
|
Sign up to set email alerts
|

Quality Teaching: The Perspectives of the Jordanian Inclusive Primary School Stakeholders and the Ministry of Education

Abstract: The aim of this study was to compare and contrast the Jordanian school stakeholders' perspectives of quality teaching with the Ministry of Education's perception looking particularly at potential differences in interpretation. Interview and documents analysis techniques were used. The sample of the study was seven primary school teachers and their six principals. Each perspective has been presented. Comparison and contrast has been made to highlight the similarities and differences between the two perspectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Like many countries in the developing world, Jordan has adopted inclusion as part of larger education reforms intended to increase access for all students. The comparative literature review has revealed while the structure of inclusion has transferred into Jordanian laws, the policies have neglected to include pragmatic details of how to implement the practice (McBride & Al Khateeb, 2010;Sakarneh, 2014). The policy to practice gap cited in systemwide analyses such as that undertaken by McBride and Al Kahteeb (2010), cannot be solved through either-or research that only addresses resources or attitudes, but must explore both resources and cultural beliefs as attitudes impacting inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Like many countries in the developing world, Jordan has adopted inclusion as part of larger education reforms intended to increase access for all students. The comparative literature review has revealed while the structure of inclusion has transferred into Jordanian laws, the policies have neglected to include pragmatic details of how to implement the practice (McBride & Al Khateeb, 2010;Sakarneh, 2014). The policy to practice gap cited in systemwide analyses such as that undertaken by McBride and Al Kahteeb (2010), cannot be solved through either-or research that only addresses resources or attitudes, but must explore both resources and cultural beliefs as attitudes impacting inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies revealed teachers were unwilling and reluctant to implement inclusion because they did not feel they were prepared with adequate resources and training, but did not cite cultural beliefs (Al Jabery & Zumberg, 2008;Al-Natour et al, 2015;Amr, 2011;Siam & Al-Natour, 2016). Empirical studies indicated the availability of resources influences teacher attitudes, however interviews with teachers conducted by Sakarneh (2014) indicate there is a cultural dimension to how teachers make sense of their roles and perceive students with special needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably more research from -the medical perspective-have been done in this area, but less research -from educational perspective-has been conducted. It has been reported that these sensory char-acteristics can influence student behaviour during the teaching-learning process (Caplan, Feldman, Eisenhower & Blacher, 2016;Sakarneh, 2014a). Sensory characteristics of children with ASD may also hinder their interaction and restrict them from acting effectively during their communications with others (Dugas et al, 2018;Samson, Phillips, Parker, Shah, Gross, & Hardan, 2014;Tomchek & Case-Smith, 2009;Watson, Patten, Baranek, Poe, Boyd, Freuler, & Lorenzi, 2011).…”
Section: Introductionmentioning
confidence: 99%